2012
DOI: 10.1111/geb.12001
|View full text |Cite
|
Sign up to set email alerts
|

What determines the climatic niche width of species? The role of spatial and temporal climatic variation in three vertebrate clades

Abstract: Aim Climatic niche breadth (the range of climatic conditions that a species experiences over space and time) is a fundamental topic in ecology, biogeography and evolution. But what determines the climatic niche width of species? In 1967, Janzen suggested that climatic niche widths for temperature were determined by levels of seasonal fluctuation in temperature at each locality, such that niche breadths are narrow in tropical species and broad in temperate species. However, it is unclear whether climatic niche … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
123
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(138 citation statements)
references
References 53 publications
(64 reference statements)
13
123
0
Order By: Relevance
“…Previous work has shown that niche breadth is strongly influenced by local climatic seasonality [34]. Therefore, a combination of narrower niches [6], less historical exposure to climatic changes [1,8] and potentially, greater importance of biotic interactions limiting species distributions and hence their ability to shift their ranges [50], have probably interacted to result in migration not evolving as frequently in species occurring in tropical latitudes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that niche breadth is strongly influenced by local climatic seasonality [34]. Therefore, a combination of narrower niches [6], less historical exposure to climatic changes [1,8] and potentially, greater importance of biotic interactions limiting species distributions and hence their ability to shift their ranges [50], have probably interacted to result in migration not evolving as frequently in species occurring in tropical latitudes.…”
Section: Discussionmentioning
confidence: 99%
“…The median and variance of these points along the first two environmental axes of the PCA was then measured using the 'ecospat' package in R [33]. We multiplied the variances from PC1 and PC2 in each season to obtain a measure of niche breadth (area) and then calculated the sum of these values as an estimate of total niche breadth of each study species [33,34].…”
Section: (C) Seasonal Niche Overlap and Niche Breadthmentioning
confidence: 99%
“…1). In a recent study, Quintero and Wiens (2013a) suggested that local seasonal temperature variations are the main factors determining the niche breadth of some plethodontid species. Not surprisingly, and as shown by annual and grouped extreme climatic values in areas where P. cinereus is found, low-temperature extremes were observed in the Canadian provinces of Ontario and Québec, and high-temperature extremes were observed in the American states of Indiana, Virginia and North Carolina, in the southern part of the species' range (Table 2; Fig.…”
Section: Current Distribution and Climatic Niche Of Plethodon Cinereusmentioning
confidence: 99%
“…Because the costs of maintaining thermal tolerance to high temperatures do not allow species to invest in thermal tolerance to low temperatures, species will display low thermal breadth and low thermal complementarity, which should decrease community thermal breadth. According to the climatic variability hypothesis (Stevens, 1989), species occurring in more variable climates should have broader thermal tolerances (e.g., Addo-Bediako et al, 2000;Quintero and Wiens, 2013;Khaliq et al, 2014). Support for this hypothesis comes from a variety of taxonomic groups-both endotherms and ectotherms-found along climatic and latitudinal gradients (e.g., Addo-Bediako et al, 2000;Quintero and Wiens, 2013;Khaliq et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…According to the climatic variability hypothesis (Stevens, 1989), species occurring in more variable climates should have broader thermal tolerances (e.g., Addo-Bediako et al, 2000;Quintero and Wiens, 2013;Khaliq et al, 2014). Support for this hypothesis comes from a variety of taxonomic groups-both endotherms and ectotherms-found along climatic and latitudinal gradients (e.g., Addo-Bediako et al, 2000;Quintero and Wiens, 2013;Khaliq et al, 2014). This hypothesis implies that communities from regions with high thermal seasonality should display high mean thermal breadth.…”
Section: Introductionmentioning
confidence: 99%